Tolerability of a comprehensive cardiorespiratory monitoring protocol in an epilepsy monitoring unit - Gehlbach, Brian K.; Sainju, Rup K.; Tadlock, Deanne K.; Dragon, Deidre N.; Granner, Mark A.; Richerson, George B. (Epilepsy & behavior, 2018)
Recent reports of fatal or near-fatal events in epilepsy monitoring units (EMUs) and an increasing awareness of the effects of seizures on breathing have stimulated interest in cardiorespiratory monitoring for patients undergoing video-electroencephalography (EEG) recording. Patient and provider acceptance of these extra recording devices has not previously been studied and may represent a barrier to widespread adoption. We queried EMU subjects regarding their experiences with a monitoring protocol that included the continuous measurement of oral/nasal airflow, respiratory effort (chest and abdominal respiratory inductance plethysmography), oxygen saturation, and transcutaneous CO2. Surveys were returned by 71.4% (100/140) of eligible subjects. Overall, 73% of participants reported being moderately to highly satisfied with the monitoring, and 82% reported moderate to strong agreement that advance knowledge of the monitoring would not have changed their decision to proceed with the video-EEG study. Except for nasal airflow, none of the additional monitoring devices caused more discomfort than EEG electrodes. Patient acceptance of an EMU comprehensive cardiorespiratory monitoring protocol is high. The information obtained from “multimodality recording” should help clinicians and investigators understand the effect of seizures on both cardiac and respiratory physiology, may enhance safety in the EMU, and may aid in the identification of biomarkers for sudden unexpected death in epilepsy (SUDEP). •In patients admitted to an epilepsy monitoring unit, acceptance of a comprehensive cardiorespiratory monitoring protocol was high.•Most participants reported no interference with sleep or daily activity with multimodal recording.•These data provide evidence that the institution of new cardiorespiratory monitoring procedures by EMUs would be widely accepted, increasing both the yield and safety of long-term video-EEG monitoring.